PERLINDUNGAN HUKUM TERHADAP DESAIN INDUSTRI GERGAJI MESIN MENURUT UU NO. 31 TAHUN 2000 TENTANG DESAIN INDUSTRI - Dwi Aryani, (2011)
Regulation of the protection on Industrial Design related to chainsaw provided by Law number 31 of 2000 on Industrial Design. Protection of Industrial Design are intended to protect creation based on the principle of the first person who apply the Industrial Design to the Directorate General of Intellectual Property or referred to the principle of first to file. The term of protection of Industrial Design over 10 years from the date of receipt and cannot be extended, protection of the Industrial Design that has been registered is absolutely necessary to prevent piracy and recognition of ownership by other people of the industrial design. In this case the writer intends to describe how the procedures for registration of Industrial Design and try to explain the settlement of disputes in the case of Industrial Design, which has been decided by the Central Jakarta Commercial Court.